Metastatic melanoma patient outcomes since introduction of immune checkpoint inhibitors in England between 2014 and 2018. Issue 4 (12th September 2020) - Board, Ruth; Smittenaar, Rebecca; Lawton, Sarah; Liu, Hanhua; Juwa, Bukky; Chao, David; Corrie, Pippa
Abstract: Immune checkpoint inhibitors (CPIs) have radically changed outcomes for patients diagnosed with metastatic melanoma globally in the last 10 years, based on evidence of overall survival (OS) benefits generated from international randomised controlled trials (RCTs). Since RCTs do not always reflect real‐world prescribing, we interrogated established national databases to track prescribing of CPIs approved for first line treatment of metastatic melanoma patients in England since 2014 and determined patient outcomes associated with OS, as well as treatment‐related toxicity. Between April 2014 and March 2018, 5465 melanoma patients were diagnosed and treated with systemic anticancer therapy (SACT), 2322 of which received first‐line CPIs. There was good 3‐year OS concordance with RCT outcomes for ipilimumab (32%), ipinivo (56%) and nivolumab (51%), but OS was lower than expected for pembrolizumab (40%). Comparing patients prescribed ipinivo with those prescribed pembrolizumab, ipinivo‐treated patients were younger (88% vs 49% patients <70 years, P < .001) and fitter (60% vs 38% patients with Eastern Cooperative Oncology Group [ECOG] performance status 0, P < .0001). Emergency hospital admission rates from the earliest and last treatment dates were higher for patients prescribed ipinivo (37% and 55%) compared to those prescribed pembrolizumab (17% and 29%). The 30‐day mortality rates favoured ipinivo patients (3.8% ipinivo, 9.1% pembrolizumab, P < .0001) and likely reflected marked differences in median treatment durations: 63 (range 7‐440) days for ipinivo and 192 (range 5‐943) days for pembrolizumab. The dominant treatment‐related condition linked to hospital admission was colitis, recorded for 25% of patients prescribed ipinivo compared to 4% of patients prescribed pembrolizumab. Our population data has demonstrated that RCT outcomes can be achieved in routine care settings with careful patient selection. Abstract : What's new? Immune checkpoint inhibitors (CPIs) greatly impact overall survival in metastatic melanoma. In England, CPIs have been used as first‐line therapy for this malignancy since 2014. This retrospective study assessed survival and toxicity among English metastatic melanoma patients prescribed CPIs between 2014 and 2018. For the CPIs ipilimumab, nivolumab, and ipinivo, survival outcomes were remarkably similar to registration trials. Poorer outcomes were associated with pembrolizumab, possibly because patients who received this drug were older and relatively less fit. Ipinivo generated the highest rates of emergency hospital visits and admissions, although 30‐day mortality was unchanged, potentially reflecting effective management of complications.